Kata Sapaan dalam Bahasa Minangkabau di Kenagarian Tuik IV Koto Mudiak Batang Kapeh Kabupaten Pesisir Selatan - Utama, Fefriadi Rangga; Emidar, Emidar; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article aims to (1) to describe form of using address form based on matrilineal progeny in Minangkabaunesee in Tuik IV Koto Mudik region. (2) to describe form and using address form based on marriage in Minangkabaunesee in Tuik IV Koto Mudik region, and (3) to describe the form and using no kinship address form, include tradition address form, religion address form, and job position in Minangkabaunesee in Tuik IV Koto Mudiak region, Batang Kapas sub-district, Pesisir Selatan district. This research is qualitative research by using descriptive method. The research data is address form in Minangkabaunesee in Tuik IV Koto Mudik region Batang Kapas sub-district Pesisir Selatan district. The source of this research is verbal source as a primary source uttered by informant as native speaker. The data is collected by using listening method, recording technique and writing technique as continuation technique. The research finding is 23 matrilinial kinship address forms, 32 kinship address form based on marriage, whereas no kinship address form are found 10 job position address form, 8 religion address form, and 3 tradition address forms in Minangkabaunesee in Tuik IV Koto Mudik region Batang Kapas sub-district, Pesisir Selatan district.